2014
DOI: 10.1039/c4cp03342f
|View full text |Cite
|
Sign up to set email alerts
|

PbS sensitized TiO2nanotube arrays with different sizes and filling degrees for enhancing photoelectrochemical properties

Abstract: PbS nanoparticles (PbS NPs), an efficient sensitizer for TiO2 nanotube arrays (TiO2 NAs), were fabricated by the method of sonication-assisted successive ionic layer adsorption and reaction (SILAR). The filling degree and size of PbS NPs can be tuned by changing the repeated cycles (N) of the SILAR process. TiO2 NAs can be fully covered with PbS NPs with a size ranging from less than 4 nm to 25 nm and large aggregates inside and outside the nanotubes when N reaches 15. The growth mechanism of PbS NPs in TiO2 N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 39 publications
(33 reference statements)
0
14
0
Order By: Relevance
“…And PbS NPs also can be attached to TiO 2 NAs by a sonicationassisted SILAR method [9]. So, we believed that nanoscale Bi 2 S 3 and PbS can be successively deposited on TiO 2 NAs using two methods mentioned above.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…And PbS NPs also can be attached to TiO 2 NAs by a sonicationassisted SILAR method [9]. So, we believed that nanoscale Bi 2 S 3 and PbS can be successively deposited on TiO 2 NAs using two methods mentioned above.…”
Section: Resultsmentioning
confidence: 99%
“…[13] and [14], PbS NPs of 4 nm or lower has a more negative CB than that of TiO 2 . Previously, we found that PbS NPs (\4 nm) can be fabricated using a sonication-assisted SILAR method when cycle number (n) is 5 [9]. Figure 4a schematically illustrates energy band diagram of PbS, Bi 2 S 3 , and TiO 2 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This as‐prepared heterostructure exhibited the ability to capture light range from UV to near‐infrared, and led to chemically degrade various organic pollutions. Besides, chalcogenide compounds including ZnIn 2 S 4 , CuInS 2 , Ag 2 S, In 2 S 3 , PbS, CdSe, MoS 2 , BiS 3 are all utilized for creating heterostructures . 3D hierarchical configurated MoS 2 NS@TiO 2 NB was reported by Zhang and co‐workers via a traditional hydrothermal method, which showed unexceptionable photocatalytic H 2 production activity due to the matched energy level between TiO 2 and MoS 2 , and as a result, the recombination of photogenerated e − –h + pairs was suppressed (Figure c,d,g,h).…”
Section: Strategies In Improving Nanostructured Tio2 Based Materials mentioning
confidence: 99%